Biosynthesis of Polyunsaturated Fatty Acids in Marine Invertebrates: Recent Advances in Molecular Mechanisms - Juan C. Navarro (Marine Drugs, 2013)
Virtually all polyunsaturated fatty acids (PUFA) originate from primary producers but can be modified by bioconversions as they pass up the food chain in a process termed trophic upgrading. Therefore, although the main primary producers of PUFA in the marine environment are microalgae, higher trophic levels have metabolic pathways that can produce novel and unique PUFA. However, little is known about the pathways of PUFA biosynthesis and metabolism in the levels between primary producers and fish that are largely filled by invertebrates. It has become increasingly apparent that, in addition to trophic upgrading, de novo synthesis of PUFA is possible in some lower animals. The unequivocal identification of PUFA biosynthetic pathways in many invertebrates is complicated by the presence of other organisms within them. These organisms include bacteria and algae with PUFA biosynthesis pathways, and range from intestinal flora to symbiotic relationships that can involve PUFA translocation to host organisms. This emphasizes the importance of studying biosynthetic pathways at a molecular level, and the continual expansion of genomic resources and advances in molecular analysis is facilitating this. The present paper highlights recent research into the molecular and biochemical mechanisms of PUFA biosynthesis in marine invertebrates, particularly focusing on cephalopod molluscs.